Distribusi Linux Untuk STMIK Bina Sarana Global dengan Metode Remastering - Dzulhaq, Muhammad Iqbal; Putra, Eko Susilo Yulianto (JURNAL SISFOTEK GLOBAL, 2014)
This research is related to Linux, one of the operating systems that are included in the category of open source. OpenSource is a term for software which source code is provided developers for distribution in general in order to learn how it works, modified or further developed and distributed. Over time, Linux is growing very rapidly to create kinds of distribution, with a variety of features and ease of configuration. This thesis discusses the design production of distributed Linux that focus on light desktop is intended to be an alternative software alternate imitation of software still used in STMIK Bina Sarana Global. This distribution is developed using remastering with Xubuntu distro as a base. It is intended that distributions are easy to develop back. This distribution is named GOES OS. Creating of distributions using a structured phase begins with the concept of making, needs analysis, design distro, repository elections, elections create an application package file and a configuration script to the stage of making LiveUSB and Installer. Results of this research is LiveUSB and installer that can be run without having to install or can directly attach it to the hardisk and in distro contain alternative applications that alternate imitation of application commonly use male and female students on campus.